Enhancing advanced motor skills through small-sided game-based physical education learning - Nurman Hadi; Nurul Ihsan; Anton Komaini; Sefri Hardiansyah (Global Econedu, 2026)
This study aimed to examine the effect of small-sided game-based learning on the advanced motor skills of seventh-grade students at SMP Negeri 05 Kepahiang, Indonesia. The study employed a quantitative approach using a pre-experimental one-group pretest–posttest design involving 32 seventh-grade students selected through total sampling. Advanced motor skills were assessed through five components, namely speed, agility, lower-body explosive strength, balance, and coordination. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-sample t-test. The findings revealed improvements across all motor components following the intervention. The composite motor skill score increased from a pretest mean of −0.001 to a posttest mean of 3.967. The paired-sample t-test demonstrated a statistically significant difference between pretest and posttest scores (t = −17.266, p < 0.001). Small-sided game-based learning effectively enhanced students' advanced motor skills and can be considered an innovative pedagogical strategy for promoting multidimensional motor development in junior secondary school physical education